RETRACTED ARTICLE: Implementation of thermal aware wireless sensor network clustering algorithm based on fuzzy and spider optimized cluster head selection - Priya, R. Karpaga; Venkatanarayanan, S. (Journal of ambient intelligence and humanized computing, 2021)
In a modern approach, a smart grid requires an innovation on various fronts such as a wireless sensor network which is an important component of smart grid applicability. To fulfill the Quality of Service (QoS) needs in smart grid network, a structure of network and topology should be optimized especially in the urban areas. The clustering methodologies are useful technique for optimizing network topologies. In clustering, the clustering process consists of cluster head node selection and rotation which is based on Residual Energy, Distance of node from base station etc. However, the impact of temperature rise has not been considered so far. Based on the previous related works, this paper proposes a Thermal Aware solution based on combining Eigen Centrality Fuzzy Cluster size Control and Spider Optimization Algorithm . Furthermore, an influence of temperature can be realized through Received Signal Strength (RSS) and the number of packets received. The proposed algorithm is simulated in MATLAB and implemented in hardware test bed using Zigbee and PIC microcontroller. Consequently, the result confirms the impact of thermal heat on Cluster Head selection control and also the prediction of number of rounds.